9-7x=42+(-4x)

Simple and best practice solution for 9-7x=42+(-4x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-7x=42+(-4x) equation:


Simplifying
9 + -7x = 42 + (-4x)

Solving
9 + -7x = 42 + (-4x)

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '(4x)' to each side of the equation.
9 + -7x + (4x) = 42 + (-4x) + (4x)

Combine like terms: -7x + (4x) = -3x
9 + -3x = 42 + (-4x) + (4x)

Combine like terms: (-4x) + (4x) = 0
9 + -3x = 42 + 0
9 + -3x = 42

Add '-9' to each side of the equation.
9 + -9 + -3x = 42 + -9

Combine like terms: 9 + -9 = 0
0 + -3x = 42 + -9
-3x = 42 + -9

Combine like terms: 42 + -9 = 33
-3x = 33

Divide each side by '-3'.
x = -11

Simplifying
x = -11

See similar equations:

| 3x^2-58x-40=0 | | 3ab-2b=3a-b | | -3x^2-3x+90=0 | | 1.2y-0.3x=0.12 | | -7x-5y=11 | | X/11=-22 | | f(x)=2x^2-16x+27 | | 3Y-9-3Y=-9 | | 1.2x-0.3y=0.12 | | 12-7x=9x-5x-87 | | 4x^3+72x^2+68x=0 | | 5/6-x/6=6/5 | | 2^3*x=1/64 | | 3x-5x+4-x+7=88 | | -3x+8=5x-2 | | -x^3+10x^2+39x=0 | | 3x-7=3(x-3)+3 | | ln(x+5)=ln(x-4)-ln(x+4) | | a-1/2=2a-2/3 | | 4x+15x+6=3x-14 | | 19+20m+m^2= | | 24x+8x^2+2x^3=0 | | .4w-.3w+.4w=3 | | 3(2x-5)=5(x-4+x) | | 9c^3+12c^2=0 | | 4x^3-48x^2+140x=0 | | 100/10= | | 5(7x+1)=320 | | 3x+2x+3+5x-13=180 | | 2c+4d=8 | | 45m-90=90m | | P=5s-(100-2s) |

Equations solver categories